2017
DOI: 10.1186/s12914-017-0134-2
|View full text |Cite
|
Sign up to set email alerts
|

Online surveillance of media health event reporting in Nepal: digital disease detection from a One Health perspective

Abstract: BackgroundTraditional media and the internet are crucial sources of health information. Media can significantly shape public opinion, knowledge and understanding of emerging and endemic health threats. As digital communication rapidly progresses, local access and dissemination of health information contribute significantly to global disease detection and reporting.MethodsHealth event reports in Nepal (October 2013–December 2014) were used to characterize Nepal’s media environment from a One Health perspective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…Our study showed that the official sources were more likely to report events related to livestock compared to humans. This finding is in agreement with a previous study carried out in Nepal where international sources, especially OIE, were more likely to report animal health events compared to human events [ 26 ]. OIE member countries have requirements for reporting unusual events related to notifiable diseases [ 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our study showed that the official sources were more likely to report events related to livestock compared to humans. This finding is in agreement with a previous study carried out in Nepal where international sources, especially OIE, were more likely to report animal health events compared to human events [ 26 ]. OIE member countries have requirements for reporting unusual events related to notifiable diseases [ 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…In this study, journalists reported on public health topics most frequently, followed by animal health and environmental health, respectively. Our findings were also in line with previous research that revealed a priority on human health event reporting and an underreporting of animal and environmental health events from a global digital epidemiology standpoint in Nepal [34].…”
Section: Discussionsupporting
confidence: 92%
“…While the significance of health communication and communication technologies in public health is well recognized, it is underutilized in veterinary and environmental health sciences [ 32 , 33 ]. A recent study of One Health reporting in Nepal revealed few animal and environmental health media reports were captured by an online, global electronic information system, demonstrating either a low sensitivity for health reports from these sectors or an underreporting of these topics from the Nepali media [ 34 ]. Animal and environmental health, however, are directly linked to human health; therefore, the depiction of these in the media is highly relevant to readers and subsequent public knowledge, especially for those in low-resource settings who may not have access to other sources of information.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive work has examined the value of Internet-based sources such as social media, search engines and news contents for conducting infectious disease surveillance 9–11 . Some studies have focused on confined geographical locations, such as Latin America 12 , the Netherlands 13 and Nepal 14 , while others have analyzed disease outbreaks globally 15,16 .…”
Section: Introductionmentioning
confidence: 99%